INVESTIGASI TERHADAP KEBERADAAN SURAT UTANG NEGARA - Mutia Evi Kristhy; Ariel Adolfo Kesaulya; Daniel Jeffry Rivaldo; Dewata Napulangit; Dicky Hernando Setiawan; Dimas Prayoga; Gabriel Elia Sahala Pandiangan; George Mikhael Marsall; Linda Kumala; Paska; Jaga Taka Pedro Gonzales (Jurnal Komunikasi Hukum, 2022)
The government is the basic sector which is expected to be able to become a driving force in the economic development sector, by utilizing several existing sources of financing, one of which is state debt securities. about government bonds. Government bonds are financial instruments whose payments use the interest system.